An Innovative Technique for Rapid Screening of Cigarette Filter Adsorbents. Issue 1 (27th October 2016) - Branton, Peter; Leistner, Matthias; Wöllner, Michelle; Kaskel, Stefan
Abstract: Cigarette smoke is an aerosol containing a large number of chemicals, including toxicants. In recent years, a number of cigarette filter additives have been evaluated for their toxicant filtration properties. Screening is a useful tool to accelerate the testing and development of new filter additives and filtration mechanisms. The evaluation of a filter material screening technique based on the so‐called InfraSORP technology is described. By comparing InfraSORP measurements with reference cigarette smoke experiments of potential cigarette filter materials like activated carbons and ion‐exchange resin, an excellent correlation is demonstrated. This technique allows for a rapid screening of potential filter materials prior to testing any final candidates in cigarettes. Abstract : An innovative screening tool named InfraSorp for the rapid evaluation of toxicant reduction by porous filter materials is introduced. Based on the optical detection of released heat during the adsorption of toxic molecules, reliable information is obtained within a few minutes with good correlation between the InfraSORP measurements and the reference cigarette smoke filter experiments.